The Effect of Board Diversity on Performance Mediated by Company Risk in Consumer Cyclicals Companies - Putri, Fara Ghassani; Muchtar, Susy (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This research aims to analyze the influence gender on board directors and commissioners on company performance. The data used in this research is secondary data sourced from the annual reports of consumer cyclicals companies listed on the Indonesia Stock Exchange (BEI) during the 2019 - 2023 period. The research sample was selected using a purposive sampling method so that 80 companies were sampled. The data analysis used to test the hypothesis is panel data regression analysis using the Eviews 9 program. The research results show that Gender Diversity has no effect on ROA and Share Prices. Board Independence has no effect on ROA and has a negative effect on share prices. Board Size has a positive effect on ROA and Share Prices. Institutional Ownership has a positive effect on ROA and Share Prices. Liquidity has no effect on ROA and share prices. Gender Diversity has a negative effect on the Debt To Assets Ratio. Board Independence has no effect on the Debt To Assets Ratio. Board Size has no effect on the Debt To Assets Ratio. Institutional Ownership has no effect on the Debt To Assets Ratio. Gender Diversity has a negative effect on ROA and Share Prices which is mediated by the Debt To Assets Ratio. Board Independence has no effect on ROA and Share Prices which are mediated by the Debt To Assets Ratio. Board Size has no effect on ROA and Share Prices which are mediated by the Debt To Assets Ratio. Institutional Ownership has no effect on ROA and Share Prices which are mediated by the Debt To Assets Ratio.